ARKETIPE KOMERING DALAM CERPEN “JANGAN TATAP SUKUKU” KARYA OKSA PUKO YUZA (Komering Archetype in “Jangan Tatap Sukuku” By Oksa Puko Yuza) - Budi Agung Sudarmanto (Kandai, 2017)
Archetype is a form of universal thought (idea) that contains of huge emotion. Archetype constitutes a permanent deposit or collective unconsciousness in psyche (soul) from the constantly repeated for many generations. Archetype consists of persona, anima and animus, and shadows. The short story “Jangan Tatap Sukuku” describes archetype of Komering society (tribe). By using psychological literature approach, those archetypes are found. Persona is related to the general description of Komering society represented by Yuza. Anima and animus are the interchangeable side of Yuza’s femininity and Risti’s masculinity. Shadows relates to the stereotype of Komering society as collectivity, and some individual cases as individual representation of Komering tribe.